Sport as a means of coping with negative feelings for young people - Tsyuy S.; Voronova A.E.; Namazifard M.; Zakharova A.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to examine the impact of physical activity on anxiety, depression, and stress in young individuals through a meta-analysis. Methods and structure of the study. A comprehensive literature review was conducted through a systematic search of electronic bibliographic databases, including PubMed, Web of Science Core Collection, MEDLINE, and Google Scholar. The PICOS method was employed for the systematic review, while the meta-analysis method was utilized for the quantitative synthesis of the collected data. The impact of physical activity on depression and anxiety was quantified, and a synthesis analysis was performed using a random effects model. The meta-analysis employed statistical indicators such as Tau2, Chi2, I2, and Z. Results and conclusions. The results of the analysis showed a significant reduction in levels of depression and stress with the use of exercise. Physiologically, exercise promotes the release of neurotransmitters (endorphins and dopamine), which help improve mood and relieve depression [3]. Physical education classes have a positive effect not only on a persons psychological state, but also allow them to improve many functions of the body, increase a persons immunity, and improve the organization of work and rest.